A scoping review of Delphi studies concerning social participation of refugees in health services - Joacim Larsen; Henrik Eriksson; Ann Hägg Martinell (JAMK University of Applied Sciences, 2021)
The ability to appropriately attend to refugee health needs in the countries that are receiving them is an enormous institutional challenge. The varying practicalities of administering refugee health services can affect a refugee's mental health outcome during the adjustment period to their new home country. This is a report on a study undertaken to overview Delphi method approaches used to investigate the consensus by experts on the issue of refugees' social participation in health services. The review was conducted from March to December 2018 by two evaluators utilizing a systematic search strategy in presently available electronic databases. Only Delphi studies concerning forced adult refugee's social participation in health services were included, while studies that focused on children, minorities, immigrants, migrants, asylum seekers, etc., as well as studies that did not utilize the Delphi technique, were excluded. Ten peer-reviewed articles were included in the final charting of the data. The results show that Delphi approaches regarding refugee social participation have focused on important factors important for providing quality health care, health care priorities, barriers preventing social participation, and research priorities. The experts make clear that bureaucratic procedures, cross-cultural communication and empowerment, be taken into consideration when creating policies, in practice and in research. The conclusion is that by emphasizing the tacit knowledge of experts, the Delphi method can contribute to a deeper understanding of policy priorities and responsive health services.